Características da chuva e perdas de solo por erosão hídrica em diferentes sistemas de manejo do solo - MARTINS, Jennifer Caroline Vilalba; MONTEIRO, Felipe das Neves; Fanaia, Elianay da Cruz Henrique; NASCIMENTO, Maryanne Ramos; ROCHA, Rayssa Albuquerque; MENEZES, Roniedson da Silva (ANAIS DO ENIC, 2024)
-